Myocardial revascularization effects on vascular endothelial growth factor and transforming growth factor β-1 in coronary heart disease patients - I. V. Sergienko; A. E. Semenova; V. P. Masenko; L. I. Habibullina; S. A. Gabrusenko; V. V. Kukharchuk; Yu. N. Belenkov (Кардиоваскулярная терапия и профилактика)
Aim. To assess the dynamics of vascular endothelial growth factor (VEGF), transforming growth factor-beta (TGF- 1) and VEGF receptor Flt-1 (sFlt-1 or sVEGF-R1) levels in coronary heart disease (CHD) patients before and after myocardial revascularization. Material and methods: We examined fasting serum VEGF, TGF-β1 and sVEGF-R1 concentrations in 40 CHD patients (main group) 1 day before and 6 days after successful myocardial revascularization (percutaneous coronary intervention, PCI – 75%; grafting bypass surgery – 25%). Control group included 30 healthy volunteers, with fasting blood samples taken once. Results: Serum levels of VEGF and TGF-β1 in controls were 166,9±96,9 and 120±32,4 pg/ml, respectively. Before myocardial revascularization in CHD patients, VEGF level was 192,4±166,1 pg/ml, and TGF-β1 level was 11±4,9 pg/ml. There was no significant difference in basic serum levels of VEGF (p=0,4), but TGF-β1 levels were significantly lower in CHD patients, comparing to controls (р<0,0001). sVEGF-R1 levels were very low in main (0,3 pg/ml) and control (0,2 pg/ml) groups (р>0,05). After myocardial revascularization, the levels of VEGF, TGF-β1 and sVEGF-R1 were 264,7±226,6, 11,7±4,9, and 0,2 pg/ml, respectively. There was a significant increase in VEGF levels (р=0,066), without any substantial changes in TGF-β1 (р>0,05) and sVEGF-R1 (р>0,05) levels 6 days after revascularization. VEGF level reduction was observed in 6 out of 30 (20%) patients after PCI and in 2 out of 10 (20%) patients after grafting bypass surgery. In the other cases, post5revascularization VEGF level increased significantly, due to intra-revascularization transient myocardial ischemia. Conclusion: Myocardial ischemia increased VEGF levels and decreased TGF-β1 levels, not affecting sVEGF-R1 concentration.